Mycobial contamination and mycotoxinogenesis of Tinospora cordifolia: an important medicinal plant of India - Sharma, S; Sumbali, G; Sharma, V (International Journal of Agricultural Research, Innovation and Technology, 2014)
An investigation of mycoflora and associated mycotoxins was carried out from dried market samples of stem portions of Tinospora cordifolia, an important medicinal plant of India. These samples were collected from various wholesale and retail shops of eight districts of Jammu and Kashmir state viz., Kathua, Jammu, Udhampur, Rajouri, Poonch, Doda, Srinagar and Leh. A total of 39 fungal species representing 18 genera were recovered by using surface washing technique. Assessment of mycobial load of T. cordifolia showed the presence of many such fungal species that are widely acknowledged as the most important mycotoxin producers. Analyses of samples for mycotoxin contamination was done by multimycotoxin detection method. The dried samples of Tinospora cordifolia were detected to be contaminated with aflatoxin B1, aflatoxin B2, ochratoxin A, patulin and citrinin. Among the various mycotoxins detected, aflatoxins were present in maximum number of samples, which is probably because Aspergillus flavus was recovered from all the investigated samples. However, fusarial species and their toxins were not detected from the investigated samples. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17839 Int. J. Agril. Res. Innov. & Tech. 3 (2): 16-21, December, 2013